Rethinking the relationship between momentum and sport performance: Toward an integrative perspective. (May 2017) - Briki, Walid
Abstract: The relationship between momentum and performance has elicited the curiosity of athletes, coaches, and sport psychologists since the late 1970s. Psychological momentum and behavioral momentum reflect both an impetus expected to entail changes in performance. This article aims to provide an integrative perspective of momentum that is guided by three core principles. Firstly, psychological momentum and behavioral momentum represent two distinct facets of a same phenomenon, called psycho-behavioral momentum (PBM), which mediates the relationship between early and subsequent success. Secondly, PBM reflects a composite phenomenon associating psychological, physiological, and behavioral constructs. Thirdly, PBM reflects a complex and dynamical phenomenon that may take place within different and interconnected time-scales. Additionally, the present perspective proposes to rethink the way of examining the relationship between PBM and sport performance, and encourages considering the distinction between behavioral performance (i.e., internal to the PBM process) and competitive outcomes (i.e., external to the PBM process). Highlights: Psycho-behavioral momentum (PBM) represents the combination between psychological momentum and behavioral momentum. PBM corresponds to an impetus expected to entail changes in performance. PBM mediates the relationship between early and subsequent success. PBM reflects a historically embedded phenomenon taking place within different time-scales.